‘Bearded men singing psalms’: The Work of DRC Ministers as Support Services during the South African War (1899-1902) (Historia, 2023)
Considering the importance of the Dutch Reformed Church (DRC) to most facets of Boer life during the South African War (1899-1902), there has been surprisingly little inquiry into the roles played by DRC ministers in the (informal) network of Boer support services during this conflict. While some social historians and church historians have delved into the significance of religion to both the fighting men and civilians, the role of Boer religious leaders and specifically the work they performed during the war, are still largely overlooked. This article investigates how DRC ministers functioned as a form of informal support service, in the absence of a formal chaplaincy, and considers how their ability to serve both the spiritual and material needs of their congregants was directly impacted by the context in which they worked and their proximity to British oversight. To this end we use three case studies of DRC ministers who worked in three main areas impacted by the war: the Boer commandos in the field (J.D. Kestell), the British-controlled prisoner-of-war camps (A.F. Louw) and the concentration camps (A.D. Lückhoff).
Keywords: Dutch Reformed Church; South African War; field preachers; ministers; Anglo-Boer War; J.D. Kestell; A.F. Louw; A.D. Lückhoff; auxiliary support services